Digitization of the entire traffic system and mitigation of the ongoing traffic crisis across cities of developing nations - Yasar, Mohammad Samin; Rashid, Tahmid; Rhaman, Khalilur (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 35th IEEE Region 10 Conference, TENCON 2015; Holiday Inn, Sands Cotai CentralMacau; Macau; 1 November 2015 through 4 November 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/TENCON.2015.7372991